Pengembangan Media Pembelajaran E-Handout Berbasis Flipbook pada Materi Membuat Macam-Macam Kampuh - Enik Ristiana Fefrianti; Peppy Mayasari; Imami Arum Tri Rahayu; Mita Yuniati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Learning media is everything that is used to convey all information in the learning process. This research aims: (1) to determine the feasibility of flipbook-based e-handout learning media on the material for making various seam allowances (2) to determine the learning outcomes of students using flipbook-based e-handout learning media on the material for making various seam allowances. The type of research uses the ADDIE development model. The data collection instruments used in this research are: validation sheet which includes media experts, material experts, language experts, and student learning outcomes. The results the research carried out show that: 1) The development of flipbook-based e-handout learning media on the material of making various kinds of seam allowances was declared very suitable for us in learning with the results of feasibility validation carried out by 2 media expert validators, 2 material expert validators, and 2 linguist expert validators obtained overall feasibility results with an average score of 4.34 in the “Very Eligible” category. 2) The learning outcomes of students using flipbook-based e-handout learning media on the material of making various seam allowances obtained classical learning completeness of 88%.